ASSESSMENT OF BONE MINERAL DENSITY IN POSTPARTUM WOMEN AT THAI BINH MATERNITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To assess bone density in postpartum women at Thai Binh Maternity Hospital in 2026. Methods: A cross-sectional descriptive study was conducted on 112 postpartum women (currently hospitalized) at Thai Binh Maternity Hospital from August 2025 to August 2026. Results: The mean bone density in the lumbar spine and left femoral neck was 1.117±0.162 and 0.913±0.144 g/cm2, respectively. The rate of bone density reduction in the  lumbar spine and left femoral neck was 22.3% and 2.7%, respectively. Conclusion: These results reflect the significant impact of pregnancy on the remodeling of the spongy bone system. Therefore, proactive screening, nutritional counseling, and early calcium and vitamin D supplementation for women in the early postpartum period are crucial to prevent prolonged bone loss during breastfeeding.
Keywords: Postpartum women, bone density